The Role of Long Noncoding RNA AL161431.1 in the Development and Progression of Pancreatic Cancer - Ma, Gang; Li, Guichen; Fan, Wufeng; Xu, Yuanhong; Song, Shaowei; Guo, Kejian; Liu, Zhe (Frontiers in Oncology, 2021)
Pancreatic cancer is known for its notorious fast progression and poor prognosis. Long noncoding RNA (lncRNA) AL161431.1 has been reported to be involved in the pathogenesis of different cancers. In this study, we explored the role of lncRNA AL161431.1 in the development and progression of pancreatic cancer by bioinformatic analysis, in vitro and in vivo experiments in pancreatic cancer BxPC-3 and SW1990 cells, as well as clinical samples. We found that lncRNA AL161431.1 was highly expressed in pancreatic cancer cells and tissues. Knock down of lncRNA AL161431.1 led to increased cancer cell death and cell cycle arrest. Xenograft growth of SW1990 cells with stable knockdown of lncRNA AL161431.1 in mice was significantly slower than that of SW1990 cells with scrambled control shRNA. Finally, we showed the involvement of lncRNA AL161431.1 in pancreatic cancer was related to its promotion of epithelial mesenchymal transition process.